Impact of differing water hardness on the spodumene flotation. (1st October 2021) - Cao, Miao; Bu, Hao; Li, Shuangke; Meng, Qingbo; Gao, Yude; Ou, Leming
Highlights: Spodumene flotation performance was directly influenced by water hardness. Effective flotation separation could be achieved for LHW and MHW using NaOL. The key difference of LHW and MHW systems was in the flotation reagent required. The softening of water ahead of spodumene flotation was inevitable for HHW. Abstract: The objective of this study was to link water hardness to the spodumene flotation performance during the fatty acid flotation process, thus allowing a smart implementation of spodumene flotation water-use strategies in commercial plants. Batch flotation tests were conducted to study flotation performance (recovery and grade) of spodumene in fatty acid flotation system using different usage of flotation reagents and three types of water. Central composite design was used to design the experiments and response surface method was used for optimization. The results indicate that the flotation performance of spodumene is directly influenced by the use of different water samples in the fatty acid flotation system. Under appropriate flotation conditions, effective flotation separation can be achieved for low-hardness water (LHW) and medium-hardness water (MHW). The key difference between the two systems is related to the flotation reagent additions required. For the LHW sample, Na2 CO3 exerted a depression effect, but NaOH exerted an activation effect, and medium dosages of CaCl2 and sodium oleate (NaOL) were desired. For the MHW sample, high dosages of Na2 CO3 and NaOL were desired for offsetting the side reaction of calcium cations in the water sample. However, for high-hardness water, the negative effect associated with water hardness could not be addressed through controlled addition of the flotation reagent, and the softening of the water prior to flotation was unavoidable.